2006
DOI: 10.1016/j.juro.2006.04.042
|View full text |Cite
|
Sign up to set email alerts
|

The Timing of Primary Neurosurgical Repair Significantly Affects Neurogenic Bladder Prognosis in Children With Myelomeningocele

Abstract: The timing of primary neurosurgical repair has a significant impact on neurogenic bladder prognosis in children with myelomeningocele. Closure of the spinal lesion on the first day of life seems to provide the best chance for favorable lower urinary tract function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
28
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 16 publications
3
28
0
Order By: Relevance
“…A delay can have some impact on vital and functional prognoses, with higher risks of shunt malfunction and CNS infection [14][15][16][17] and worse neurogenic bladder prognosis. 18 In some patients, mostly from PALOP countries, there was a delay in MMC repair due to the unavailability of this procedure in their countries. These data corroborate the findings of Watson et al…”
Section: Discussionmentioning
confidence: 99%
“…A delay can have some impact on vital and functional prognoses, with higher risks of shunt malfunction and CNS infection [14][15][16][17] and worse neurogenic bladder prognosis. 18 In some patients, mostly from PALOP countries, there was a delay in MMC repair due to the unavailability of this procedure in their countries. These data corroborate the findings of Watson et al…”
Section: Discussionmentioning
confidence: 99%
“…In a retrospective study, early surgical intervention (<72 hours after birth) was found to be associated with a more favorable outcome in terms of urinary symptoms in patients with MMC, and investigators postulated that surgery within the first 24 hours increases the likelihood of maintaining urinary tract function15). In another study where the outcomes of prenatal (in utero) and postnatal surgery were compared, it was observed that prenatal intervention was associated with better motor development while also alleviating the need for shunt placement in most patients.…”
Section: Discussionmentioning
confidence: 99%
“…[101828] In addition to the individual patient, the consequences of delay in care pose a significant pressure on patients’ families and dependents, along with a large burden of cost to the public healthcare system. [10] Through the analysis of sources of delay in accessing medical care in low-income nations, the following themes have emerged as the fundamental causes: Cultural beliefs and practices, financial restrictions, knowledge and skills of primary care providers and the public's perception of same, and transportation.…”
Section: Introductionmentioning
confidence: 99%